ANALISIS KEBUTUHAN TERHADAP LULUSAN S2 PROGRAM STUDI PENDIDIKAN EKONOMI DI JAKARTA - Suparno Suparno (Jurnal Ilmiah Econosains, 2016)
ABSTRACT This study aimed to determine the needs of graduates S2 Economic Education Program which includes: (1) the number of applicants and the capacity of similar study programs in the last 3 years; (2) the number and the last teacher education; (3) documents graduate profile and learning outcomes (learning outcomes), the curriculum structure and distribution of similar subjects and sejenjang Prodi; (3) the structure of the curriculum and the distribution of subjects similar but different study program levels; (4) tracking studies alumnus that contains a waiting period of graduates get jobs, work field conformity with graduate skills, achievement of the graduate profile that is designed study programs in the workplace and so in the last 3 years; (5) Data job along with the necessary qualifications, and (6) estimate the number of jobs available per year. The results showed that: (1) number of applicants and the capacity program similar studies in the past 3 years has increased (2) Applicants primary education level S2 is teachers (3) Profile graduate courses Economic Education S2 is becoming educators / teacher / lecturer in economics, education personnel are qualified, researchers in the field of education and the economy, education managers, consultants, education and economics. (4) Economic Education at Bachelor (S1) there are 116 universities with 1,434 permanent lecturers and 49 526 active students. (5) Graduate Economics Education courses average S2 are people already working who want to improve or expand the choice of working careers, and (6) Data jobs for graduates S2 economic education is still a lot on the function as an educator at the College / Lecturer with amount per year of about 10 people. Keywords: Needs Analysis, S2 Graduate Study Program of Economic Education.